The Analysis Of The Development Strategy Of Chilli Pepper (Capsicum Frutescens L.) For The Improvement Of The Economy Of Farmers 'Society In Sub District Of Sungai Kakap Kubu Raya District - Rahmatullah Rizieq; Donna Youlla; Maskuri Maskuri (International Journal of Multi Discipline Science, 2018)
production and productivity. The condition of land in Kakap subdistrict of Kubu Raya District is swamp furthermore the land is affected by tidal area so that it becomes the limiting factor to get high production and productivity. This study aims to determine the condition of chili pepper business in the village of Kalimas in Sungai Kakap District of Kubu Raya. And also to formulate alternative strategy of development of chili pepper farming. In this study it is known that chili pepper farming in the village of Kalimas has internal factors that become the main strength of the ease of marketing factors of production. While the main weakness is the capital factor of farming. The external factor that becomes the main opportunity is the demand factor of chili pepper and the main threat is the attacking factor of plant disturbing organism. Through SWOT matrix analysis, it is known that internal factors that become strength and weakness are combined with external factors into opportunities and threats so that there are several alternative strategies for the development of chili pepper farming. SO strategies obtained are: Increased production through intensification and extensification, application of agribusiness farming system by partnering to subsystems of input providers and production facilities and marketing subsystems. For the WO strategy gained are: Strengthening of stakeholders through improvement of cooperation relationship with all related parties, improvement of training and socialization and optimization of production. While for strategy of ST and WT that is obtained is: efficiency of use of means of production and diversification of farming without leaving chili pepper farming.